2021
DOI: 10.1007/s10750-021-04655-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and a manipulative parasite on the swimming behaviour of Gammarus pulex in flowing water

Abstract: Numerous freshwater acanthocephalans are able to alter the behaviour of their intermediate hosts to increase their predation risk by final hosts, thereby enhancing trophic transmission between their two hosts. Because temperature is widely expected to impact freshwater host-parasite interactions, we investigated how it can affect movements of both uninfected and Pomphorhynchus laevis-infected Gammarus pulex in an artificial stream in 5 cm/s water flow. We found that P. laevis infection of G. pulex induced both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Contrastingly, field studies from the same host parasite system found little evidence that temperature modified host-parasite interaction, and highlighted the possible difference between laboratory experiments and natural settings [61]. Likewise, studies from acanthocephalan hostparasite systems have shown that temperature changes within existing and predicted distribution ranges appear to have no impact on these behavioural changes in hosts and subsequent transmission outcomes [62,63]. Altogether, these findings emphasise the stark differences across various host-parasite associations.…”
Section: Postprintmentioning
confidence: 95%
“…Contrastingly, field studies from the same host parasite system found little evidence that temperature modified host-parasite interaction, and highlighted the possible difference between laboratory experiments and natural settings [61]. Likewise, studies from acanthocephalan hostparasite systems have shown that temperature changes within existing and predicted distribution ranges appear to have no impact on these behavioural changes in hosts and subsequent transmission outcomes [62,63]. Altogether, these findings emphasise the stark differences across various host-parasite associations.…”
Section: Postprintmentioning
confidence: 95%
“…The acanthocephalan"s particular position within the food web in freshwater ecosystems requires complex biological interactions and depends on the viability of intermediate and definitive host populations (Galli et al, 1998;Hatcher et al, 2012). At their different developmental stages, acanthocephalan endoparasites are impacted either directly by their environment or indirectly through effects on their hosts (Galli et al, 2001;Hatcher et al, 2012;Fanton et al, 2021). Therefore, environmental perturbations affecting either their free-living stages or their hosts will also lead to physiological, ecological and behavioural changes for acanthocephalans (Marcogliese, 2008;Labaude et al, 2017;Sanchez-Thirion et al, 2019).…”
Section: Introductionmentioning
confidence: 99%